2014
DOI: 10.2903/sp.efsa.2014.en-697
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo genotoxicity studies on nivalenol and deoxynivalenol

Abstract: Nivalenol (NIV) and deoxynivalenol (DON) are structurally related mycotoxins produced by Fusarium fungi. These fungi typically infest cereal crops such as wheat, maize, barley, oats and rye, and NIV and DON are regularly found in cereal grains, food and feed. Recent risk assessments identified possible data gaps for both DON and NIV in particular with respect to genotoxicity and carcinogenicity. The overall objective of the project was to assess the genotoxicity of DON and NIV, including the identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In contrast, Comet assays did not detect genotoxicity due to DON in human lymphoblastoid TK6 cells and metabolically competent human hepatoma HepaRG cells . In vivo studies in mice found DON to be nongenotoxic in multiple organs and tissues using a battery of assays, including the Comet assay, Pig-a assay and micronucleus assay (Le H egarat et al, 2014). The lack of tumours and pre-neoplastic lesions in p53þ/À mice supports the conclusion that the potential for direct DNA damage due to DON exposure is low.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, Comet assays did not detect genotoxicity due to DON in human lymphoblastoid TK6 cells and metabolically competent human hepatoma HepaRG cells . In vivo studies in mice found DON to be nongenotoxic in multiple organs and tissues using a battery of assays, including the Comet assay, Pig-a assay and micronucleus assay (Le H egarat et al, 2014). The lack of tumours and pre-neoplastic lesions in p53þ/À mice supports the conclusion that the potential for direct DNA damage due to DON exposure is low.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, in vitro and in vivo genotoxicity studies of DON have been carried out by Le Hégarat et al. (). These were conducted according to the EFSA Scientific opinion on genotoxicity testing strategies applicable to food and feed safety assessment (EFSA Scientific Committee, ) in the context of a grant agreement between EFSA and the authors.…”
Section: Hazard Identification and Characterisationmentioning
confidence: 99%
“…Till now the etiology of hedgehogs is rather uncertain (OECD 2014), but comet data using rat liver samples suggest that they can be the result of mechanical-induced damage during sample preparation or substance-related cytotoxicity (Guerard et al 2014). Furthermore, they were detected using a formamidopyrimidine DNA glycosylase (FPG)-modified comet assay in different tissues of methyl methanesulfonate (MMS)-treated mice, indicating a high level of oxidized and/or alkylated bases and/or FPG lesions (Le Hégarat et al 2014). In addition, previous studies suggest that they are not diagnostic of apoptosis and should not be taken as an indication of cytotoxicity.…”
mentioning
confidence: 99%
“…The external scientific report about the genotoxicity of nivalenol (NIV) and deoxynivalenol (DON) is an excellent example of how the comet assay can be used in vivo and in vitro (Le Hégarat et al 2014). The authors performed the comet assay with and without FPG in seven organs of mice.…”
mentioning
confidence: 99%